The effect of moringa flower extract on kidney function in obese rats - Meri, Meri; Lawrence, Christopher; Wilsen, Wilsen (Jurnal Prima Medika Sains, 2023)
This study aims to measure the effect of moringa flower extract administration on kidney function and histopathological features of the kidneys of obese male Wistar puith galir rats. This research is a type of experimental quantitative research using post-test only group design. This research was conducted at the Department of Pharmacy Pharmacology Laboratory, Faculty of Medicine, University of North Sumatra and Anatomical Pathology Laboratory, University of North Sumatra. Histopathology observation of kidney tissue was done by comparing the control and treatment groups. Changes observed will be the presence of fatty degeneration (vacuolization), necrosis and hydrophic degeneration. To obtain quantitative data, scoring was performed on each change found. The research data were tabulated and then the changes found were analyzed and presented descriptively. The research data were then analyzed with the help of SPSS version 25.0. The data normality test was analyzed with the Kolmogorov-Smirnov test approach (p> 0.05). To test the significance between test groups, one-way analysis of variance or One Way ANOVA technique was conducted at 95% confidence level (p < 0.05). Further analysis or test was conducted using Post Hoc Test with LSD technique. The results of the analysis showed that the administration of Moringa flower extract at a dose of 600 mg/KgBB was effective in improving kidney function in obese Wistar white rats. This improvement can be seen through the levels of ureum, creatinine, and histological structure of the kidneys that have improved. The results of histopathological observations of kidney tissue in treatment group 3, namely moringa flower extract at a dose of 600 mg/KgBB, experienced the most significant improvement and approached the control group compared to other groups.